Analysis of the Application of Technology Based Interactive Learning Media in Elementry School Students - Alfinayanti, Nanda; Utami, Ratnasari Diah (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to analyze the application of technology-based interactive learning media at SD Muhammadiyah 1 Surakarta, focusing on how such media support the learning process and the challenges faced in their implementation. Methodology: The research uses a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation to gain insights into the use and impact of interactive media in classroom settings. Results: The results of the study show that the media used by teachers at SD Muhammadiyah 1 Surakarta in technology-based learning include Wordwall, Gamekit, videos, Quizizz, Augmented Reality (AR), and Padlet. The implementation of interactive, technology-based media has been actively carried out to support the learning process in the classroom. Teachers at the school have demonstrated the ability to develop and apply technology-based learning media independently. They not only utilize available tools but also adapt them to suit the learning material and student characteristics. This implementation reflects that SD Muhammadiyah 1 Surakarta has effectively adapted to technological advancements in education, making interactive media an integral part of innovative and engaging teaching strategies. Applications/Originality/Value: This study contributes to the understanding of how primary schools can integrate interactive digital media into the learning process effectively. It highlights both the opportunities and the practical challenges of technology adoption in classrooms and underscores the importance of institutional support such as training and infrastructure to ensure successful implementation.